Mechanical enhancement effect of the interlayer hybrid CNT film/carbon fiber/epoxy composite. (29th September 2018) - Li, Tianshu; Li, Min; Gu, Yizhuo; Wang, Shaokai; Li, Qingwen; Zhang, Zuoguang
Abstract: Floating catalyst chemical vapor deposition carbon nanotube (CNT) film was intercalated into carbon fiber (CF) prepregs to fabricate hybrid composites. The effect of CNT film thickness was studied by using a 25 μm thick film and an ultrathin 2 μm film respectively. The results showed that the ultrathin CNT film interlayer had dramatically improved the compression strength of hybrid composite by 34% compared with CF/epoxy control composite owing to the altered failure modes. The damping ratio of ultrathin CNT film hybridized composite was substantially increased by two orders of magnitude, due to the energy dissipation of numerous nanoscale interconnections and interfaces. Moreover, the interlaminar properties and water resistance of the hybrid composites were all improved. Since a small amount of CNT film can significantly enhance the mechanical properties of CF/epoxy composite, this type of hybrid composite has potential application in multifunctional lightweight structures.